Synthesis of New Camphor-Based Carbene Ligands and Their Application in a Copper-Catalyzed Michael Addition with B2Pin2 - Koppenwallner, Maximilian; Rais, Eduard; Uzarewicz-Baig, Magdalena; Tabassum, Sobia; Gilani, Mazhar Amjad; Wilhelm, René (Synthesis, 2015)
In this work the synthesis of new asymmetric camphor-based carbene ligands from camphoric acid is described. The new carbenes can be prepared directly in high yields by the sequence: regioselective arylation of the less hindered primary amine group of (+)-cis-1,2,2-trimethylcyclopentane-1,3-diamine by Buchwald–Hartwig amination, treatment with trimethyl orthoformate, and finally treatment with a benzylic halide. The resulting carbenes, incorporating an aryl and a benzylic substituent, were successfully applied as ligands in a copper-catalyzed B2Pin2 [bis(pinacolato)diboron] addition to an unsaturated carbonyl compound. Depending on the substituents dual stereocontrol was observed and one enantiomer was obtained in up to 82% ee and the opposite enantiomer in up to 78% ee.
Keywords: N-heterocyclic carbenes; copper; catalysis; Michael addition; camphor